Wide-Field Landers Temporary Keratoprosthesis in Severe Ocular Trauma: Functional and Anatomical Results after One Year - Katarzyna Nowomiejska; Dariusz Haszcz; Cesare Forlini; Matteo Forlini; Joanna Moneta-Wielgos; Ryszard Maciejewski; Tomasz Zarnowski; Anselm G. Juenemann; Robert Rejdak (Journal of Ophthalmology)
Purpose. To evaluate longitudinal functional and anatomical results after combined pars plana vitrectomy (PPV) and penetrating keratoplasty (PKP) using a wide-field Landers intraoperative temporary keratoprosthesis (TKP) in patients with vitreoretinal pathology and corneal opacity due to severe ocular trauma. Material and Methods. Medical records of 12 patients who had undergone PPV/PKP/KP due to severe eye trauma were analyzed. Functional (best-corrected visual acuity) and anatomic outcomes (clarity of the corneal graft, retinal attachment, and intraocular pressure) were assessed during the follow-up (mean 16 months). Results. Final visual acuities varied from NLP to CF to 2 m. Visual acuity improved in 7 cases, was unchanged in 4 eyes, and worsened in 1 eye. The corneal graft was transparent during the follow-up in 3 cases and graft failure was observed in 9 eyes. Silicone oil was used as a tamponade in all cases and retina was reattached in 92% of cases. Conclusions. Combined PPV and PKP with the use of wide-field Landers TKP allowed for surgical intervention in patients with vitreoretinal pathology coexisting with corneal wound. Although retina was attached in most of the cases, corneal graft survived only in one-fourth of patients and final visual acuities were poor.